(untitled) (Scientific journal of the Fergana State University, 2025)
This paper delves into the intersection of morpho-pragmatics and pragmasyntactic interpretation, two subfields of linguistics that explore how morphological forms and syntactic structures influence pragmatic meaning in communication. Morpho-pragmatics investigates the role of morphology (such as inflections, pronouns, and verb forms) in shaping the social and pragmatic aspects of communication, such as politeness, formality, and respect. Pragmasyntax, on the other hand, focuses on how the syntax of sentences, including word order and sentence structure, reflects pragmatic functions like emphasis, politeness, and speaker intentions. This paper argues that both morphology and syntax are not just vehicles for conveying literal meaning, but are deeply intertwined with the social context of communication, reflecting power dynamics, relationships, and social norms. Through an empirical analysis of real-world data from different languages - specifically English, Spanish, and Japanese - the study highlights how speakers use different morphological and syntactic strategies to achieve specific pragmatic outcomes, such as requests, apologies, and assertions. Drawing on a variety of linguistic theories, including speech act theory, politeness theory, and pragmatics, this paper demonstrates that linguistic structures cannot be understood in isolation, but must be analyzed in light of the pragmatic context in which they occur. By examining examples from both formal and informal registers of language use, the study illustrates how morpho-pragmatics and pragmasyntax shape communication by encoding not just the content of the message but also the interpersonal dynamics between speaker and listener. The findings emphasize the importance of considering both form and function in linguistic analysis and contribute to our understanding of how language functions in real-world communication.